My Sadness – Our Happiness: Writing About Positive, Negative, and Neutral Autobiographical Life Events Reveals Linguistic Markers of Self-Positivity and Individual Well-Being - Herbert, Cornelia; Bendig, Eileen; Rojas, Roberto (Frontiers in Psychology, 2019)
Objective: Narratives of autobiographical events contain rich information about an individual’s private experience, his/her deepest thoughts, feelings and emotions. The present study investigates linguistic markers of emotion expression and subjective well-being in adults during one session of positive, negative and neutral expressive writing. Participants (N=28 healthy participants, N=7 adults with depressive symptoms), all native speakers of German were instructed to write expressively about personally relevant autobiographical life events of negative, positive and neutral content. Methods: Quantitative text analysis was performed to determine the amount of emotional words, first person pronouns (singular vs. plural) and cognitive function words used in positive, negative and neutral narratives and to examine the potency of these classes of words as linguistic markers of positivity/negativity, self-reference and cognitive reappraisal. Additionally, the relationship between expressive writing and subjective well-being was explored by assessing changes in self-reported psychosomatic symptoms and in bodily and emotional awareness immediately after positive, negative and neutral writing. Results: Regarding healthy participants, negative narratives contained significantly more negative emotional words than positive or neutral narratives. However, negative narratives also contained more positive emotional words compared to negative emotional words in positive narratives. Moreover, negative narratives contained more cognitive function words than positive narratives, suggesting that healthy participants tried to reappraise negative experiences while writing about negative personal life events. Positive narratives were characterized by an increased use of positive words and of pronouns of the first person plural (“we”), supporting a positivity bias and an extension of self-reference from first person singular to plural (we-reference) during positive expressive writing. Similarly, writing about neutral events was characterized by a positivity bias. Although based on descriptive analysis only, preferential use of positive words and cognitive function words in negative narratives was absent in participants reporting depressive symptoms. Positive, negative and neutral expressive writing was accompanied by differential changes in bodily sensations, emotional awareness and self-reported psychosomatic symptoms in all participants. Discussion: The findings are discussed with respect to previous research, a self-positivity bias and a universal positivity bias in language use highlighting the relevance of these biases as markers of subjective well-being.